Le vicissitudini del perturbante nell'arte e in psicoanalisi. Felix Vallotton e Francis Bacon di Maddalena Muzio Treccani e Mario Rivardo (Materiali di Estetica. Terza serie, 2024)
In his review of "Le vicissitudini del perturbante nell'arte e in psicoanalisi" by Maddalena Muzio Treccani and Mario Rivardo, the author examines the authors' interdisciplinary approach to exploring the uncanny in contemporary art, particularly through the works of Felix Vallotton and Francis Bacon. The author highlights how the book departs from traditional clinical psychoanalytic studies to assert that art itself can be a starting point for psychological analysis. The review praises the authors' detailed comparative analyses that bridge psychoanalysis with the thematic and structural elements in the art of Vallotton and Bacon, illuminating the profound psychological undercurrents that define their works. Iossa underlines the sophisticated exploration of how line and structure in art can manifest psychological themes, ultimately extending the boundaries of contemporary psychoanalysis.
Keywords: book review; uncanny; Art; Psychoanalysis; Felix Vallotton; Francis Bacon